2017
DOI: 10.18203/2320-1770.ijrcog20171401
|View full text |Cite
|
Sign up to set email alerts
|

Study of hysteroscopic evaluation in patients with abnormal uterine bleeding

Abstract: Background: Abnormal uterine bleeding in women is the commonest presenting complaint which accounts for one third of all gynecological consultations. It not only causes discomfort, inconvenience to healthy women but also affects their quality of life and impose financial burden on them. This insists the physician to diagnose its etiology and provide appropriate treatment. Hysteroscopy guided biopsy is a simple, safe, reliable procedure in the diagnosis of abnormal uterine bleeding. The objective of the study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…A study conducted by Kathuria R et al 19 in 2014 showed results that are almost identical to ours: 40% of patients exhibited abnormalities, while 60% had normal HPE reports. According to a study by Patil SG et al 10 in 2009, proliferative phase endometrium was found to be the most common finding, which contrasts with the results of our study, where secretory endometrium was the most frequently reported histopathology. In the study of Bashir H et al 20 (2015) endometrial hyperplasia was found in 18.9% of cases, which was also concordant with observations made by Patil SG et al 10 (2009) reported 20.0% of patients had endometrial hyperplasia, but higher than that observed by Doraiswami S et al 21 (2011) in 6.11% patients and Abid M et al 22 (2014) reported endometrial hyperplasia in 5.0% patients.…”
Section: Studycontrasting
confidence: 99%
See 2 more Smart Citations
“…A study conducted by Kathuria R et al 19 in 2014 showed results that are almost identical to ours: 40% of patients exhibited abnormalities, while 60% had normal HPE reports. According to a study by Patil SG et al 10 in 2009, proliferative phase endometrium was found to be the most common finding, which contrasts with the results of our study, where secretory endometrium was the most frequently reported histopathology. In the study of Bashir H et al 20 (2015) endometrial hyperplasia was found in 18.9% of cases, which was also concordant with observations made by Patil SG et al 10 (2009) reported 20.0% of patients had endometrial hyperplasia, but higher than that observed by Doraiswami S et al 21 (2011) in 6.11% patients and Abid M et al 22 (2014) reported endometrial hyperplasia in 5.0% patients.…”
Section: Studycontrasting
confidence: 99%
“…Furthermore, the prevalence of endometrial hyperplasia peaks among perimenopausal and postmenopausal women. 10 Overall comparison of validities of Hysteroscopy and Histopathology On hysteroscopy, the overall sensitivity, specificity, positive predictive value, and negative predictive value were as follows 96.15%, 86.49% 83.33%, and 96.97% respectively. On histopathology, the overall sensitivity, specificity, positive predictive value, and negative predictive value were as follows 80%, 72.73% 92.31%, and 84.21% respectively.…”
Section: Studymentioning
confidence: 93%
See 1 more Smart Citation